Stewardship as process: a paradox perspective - Cunha, M. P.; Rego, A.; Clegg, S.; Jarvis, W. P. (European Management Journal, 2021)
Long-term stewardship is usually represented as a stable structural condition and portrayed as a source of competitive advantage to firms (including family businesses) that use it as a mode of governance. Less is known about how organizations engage with stewardship as a process. We embrace a process approach to report a case study about the unfolding of stewardship in a multi-business family group. We conclude that stewardship is a process marked by critical tensions and paradoxes; by exploring the nature of these we uncover further dimensions and responses to the paradoxes of stewardship.